Complete mitochondrial genome and phylogenetic analysis of Acanthogobius Hasta from the lower reaches of the Yangtze River - Zhiyong Zhang; Zhiwei Zhang; Fei Zhu; Chaofeng Jia; Qian Meng; Ruijian Sun; Shuyin Chen; Guojun Wu; Bo Gao; Jiapeng Huang (Mitochondrial DNA. Part B. Resources, 2019)
In this study, the mitochondrial genome of Acanthogobius hasta was fully sequenced compared to other fish species mitochondrial genome. The genome is 16,659 bp in length, including 2 ribosomal RNA genes, 13 protein-coding genes (PCGs), 22 transfer RNA genes, and a non-coding control region, the gene composition and order of which was similar to most reported from other vertebrates. Sequence analysis showed that the overall base composition is 27.8% for A, 28.0% for C, 17.4% for G, and 26.9% for T.